Child and maternal malnutrition as a cause of sudden infant death syndrome: A comparative analysis between the Commonwealth low income and high income countries from 1990 to 2019 - Luis, Michelle; Cortorreal, Rafael (Clinical medicine (London, England), 2024)
Sudden infant death syndrome (SIDS) is the terminology used for the sudden death of a baby younger than 1 year of age due to unexpected and/or unexplained causes. Although it usually happens to babies within the first 6 months of life, it can happen up to the first year of age. Child and maternal malnutrition could be part of the unexplained causes because of the dietary deficiencies, child growth failure, suboptimal breastfeeding, low birth weight and short gestation. The aim of this analysis is to compare the disparities between the Commonwealth low and high income countries with child and maternal malnutrition as a cause of SIDS. Data was extracted from Global Burden of Disease Study 2019. The number of deaths and DALYs (Disability-Adjusted Life Years) were analysed by age, year and location from 1990 to 2019 in the population of <5 years including males and females from the Commonwealth low and high income countries. To analyse the burden trend, annual percentage change (APC) was used. The number of deaths both from Commonwealth low and high income countries displayed a downward trend over time, besides that, the Commonwealth low income countries had a notorious higher number of deaths with an APC of −41.21% (95% UI: −62.63–(−12.74)) from 346.90(95% UI: 51.28–1,105.07) in 1990 to 120.12(95% UI: 10–10) in 2019. On the other hand, the Commonwealth high income countries had an APC of 47.60% (95% UI: 12.94–89.46) from 89.32(95% UI: 78.39–99.67) in 1990 to 17.66(95% UI: 14.05–21.84) in 2019. Regarding the number of DALYs, both locations exhibit a downward trend which is definitely a positive outcome, although, the Commonwealth low income countries still retain a higher number of 30,814.33(95% UI: 4,555.00–98,161.40) in 1990 to 10,670.05(95% UI: 3,847.71–26,482.71) in 2019 with an APC of −41.19% (95% UI: −62.61–(−12.73)) compared to the Commonwealth high income which demonstrated the numbers of 7,934.04(95% UI: 6,963.09–8,853.19) in 1990 to 1,568.98(95% UI: 1,248.19–1,939.84) in 2019 with an APC of 47.58% (95% UI: 12.94–89.42). The Commonwealth low income countries demonstrated higher numbers across the years even though the trend was downwards. With these comparisons, it is proven the disparities between these locations and how the health system still has to work through different mechanisms to decrease the number of deaths and DALYs. More resources need to be allocated to prevent child and maternal malnutrition so sudden infant death syndrome could be, hopefully, reduced to the lowest rate. Global Burden of Disease Collaborative Network. 2020. Global Burden of Disease Study 2019 (GBD 2019). Seattle, United States: Institute for Health Metrics and Evaluation (IHME). [Accessed Feb 20 2024]